Changes in the Characteristics of the Panggreh Village Area Due to the Relocation of Victims of Sidoarjo Mud Disaster in Indonesia - Shofwan, Moch; Handoko, V. Rudy; Darmawan, Arif (International Journal of Geography, Social, and Multicultural Education, 2024)
Sidoarjo mud disaster in Indonesia forced local residents to flee to a safe place, one of which was Panggreh Village which has an area of 171.78 hectares or 3%. As a result, the population in Panggreh Village has automatically increased. Several cases show that if there is a change or regional development in a location, then in a short time the land around it will also change progressively. The purpose of this study was to determine changes in the area of Panggreh Village due to the relocation of victims of the Sidoarjo Mud Disaster. Collecting data in this study using documentation, observation, questionnaires and literature studies. The analytical method used is quantitative descriptive analysis with a before-after analysis technique. The results showed that overall land use change in Panggreh Village has shown a significant increase which includes 4 factors or characteristics such as livelihoods, level of education, institutions and infrastructure. So it can be concluded that the Sidoarjo Mud Disaster also had an influence on regional changes in Panggreh Village. It is hoped government policies regarding land use and population can be realized in society so that there are no policy deviations starting from population growth deviant land use.